Driving Tendency is Associated with Increased Risk of Anterior Cruciate Ligament Tears in National Basketball Association Players (103). Issue 10 (31st October 2021) - Thomas, Kevin; Schultz, Blake; Cinque, Mark; Harris, Joshua; Abrams, Geoffrey
Objectives: Previous work has shown a high return to sport (RTS) after Anterior Cruciate Ligament Reconstruction (ACLR) in National Basketball Association (NBA) players. Data on performance outcomes after RTS are less clear, with some demonstrating no difference compared to controls and others showing decreased performance. Two fundamentals of basketball are driving the ball to the basket and long-range shooting. Driving involves lateral movement, whereas long-range shooting features vertical movement. The biomechanics of these two scoring approaches may affect risk of ACL injury and post-ACLR performance. The objective of this study was to investigate whether NBA players with higher drive tendency and/or higher tendency to shoot 3-point shots are more likely to tear their Anterior Cruciate Ligament (ACL) relative to controls and if they experience decreased statistical performance after returning to play. Methods: Season-level performance statistics and ACL injuries were aggregated from the 1980-2017 NBA seasons. Fifty players with isolated ACL tears during their NBA careers who had game performance data before and after injury were identified. Three-point shooting tendency was measured using the 3-point attempt rate (3PAr) statistic for each player-season. A statistical model was created to evaluate player's tendency to drive the ball to the basket. The driving tendencies of players who underwent ACL reconstruction was compared with that of other players using an independent sample t-test. The rate of ACL tears among those with high driving tendency was compared with that of other players using an independent sample t-test. To investigate whether driving tendency and three-point shooting tendency are associated with RTS outcomes, objective case-control matching was performed. The last full season before each case player's ACL injury was matched with similar seasons of two control players without history of ACL injury (figure 1). Total career points and playing minutes after RTS were compared between cases and controls using paired z-tests. Changes in driving tendency and three-point shooting tendency before injury vs after injury were compared between cases and controls using paired z-tests. Results: Players with career-average driving tendencies more than 1 standard deviation above the mean were more likely to tear their ACL than other players (0.0521 vs 0.0275, p = 0.0258) (figure 2). This represents a relative risk of 1.896. Players who experienced an ACL tear also had higher average drive tendencies than other players (p = 0.0468). There was not a significant difference between career-average 3-point attempt rate of ACLR players relative to others. There was no significant difference in total post-injury career points or career minutes between cases and controls. There was also no significant change in driving or 3-point shooting tendency after RTS compared to controls. ACL-injured players with higher driving tendency did not fall further below the performance of their controls after they returned. Conclusions: NBA players with increased drive tendency are more likely to tear their ACL. However, players who are able to return after ACL reconstruction do not underperform statistically compared to controls and do not alter their style of play compared to the normal changes seen with age.